Matematyka
pawel26
2017-06-23 02:24:24
Dodaje w załączniku,proszę o szybką odpowiedź:) Z góry dziękuję:)
Odpowiedź
laura8
2017-06-23 05:09:52

[latex]1.\a)\\frac{frac{1}{4}-frac{1}{3}-frac{1}{6}}{frac{1}{8}-frac{1}{5}-frac{1}{10}}=frac{frac{3}{12}-frac{4}{12}-frac{2}{12}}{frac{5}{40}-frac{8}{40}-frac{4}{40}}=-frac{3}{12}:(-frac{7}{40})=-frac{1}{4}cdot(-frac{40}{7}) = frac{10}{7} = 1frac{3}{7}}[/latex] [latex]b)\\frac{frac{9}{5}:frac{3}{7}-3frac{3}{4}cdotfrac{2}{5}}{5frac{1}{4}cdotfrac{3}{7}}=frac{frac{9}{5}cdotfrac{7}{3}-frac{15}{4}cdotfrac{2}{5}}{frac{21}{4}cdotfrac{3}{7}}=frac{frac{3}{5}cdot7-frac{30}{20}}{frac{3}{4}cdot3}}=frac{frac{21}{5}-frac{3}{2}}{frac{9}{4}}=frac{frac{42}{10}-frac{5}{10}}{frac{9}{4}} = frac{27}{10}cdotfrac{4}{9}=frac{6}{5}=1frac{1}{5}[/latex] [latex]c)\\frac{1frac{1}{2}+2frac{1}{4}-frac{2}{3}cdot1,5}{0,25cdot(-2)^{2}-3frac{1}{7}cdotfrac{7}{11}}=frac{frac{3}{2}+frac{9}{4}-frac{2}{3}cdotfrac{3}{2}}{frac{1}{4}cdot4-frac{22}{7}cdotfrac{7}{11}}=frac{frac{6}{4}+frac{9}{4}-1}{1-2}}=frac{frac{15}{4}-frac{4}{4}}{-1}=frac{4}{4}-frac{15}{4} =-frac{11}{4}=-2frac{3}{4}[/latex] [latex]2.\108^{frac{1}{2}}:3^{frac{1}{2}}-3^{frac{1}{4}}cdot27^{frac{1}{4}}=(108:3){frac{1}{2}}-(3cdot27)^{frac{1}{4}}=36^{frac{1}{2}}-81^{frac{1}{4}}=\\=(6^{2})^{frac{1}{2}}-(3^{4})^frac{1}4}} =6-3 = 3[/latex]

sxsxsxsx
2017-06-23 05:11:07

Rozwiązanie w załączniku.

Dodaj swoją odpowiedź